2023
DOI: 10.3389/fcimb.2022.1059168
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of oral quercetin in hamsters infected with Leishmania Viannia braziliensis

Abstract: Leishmaniasis is a parasitic disease caused by several species of intracellular protozoa of the genus Leishmania that present manifestations ranging from cutaneous ulcers to the fatal visceral form. Leishmania Viannia braziliensis is an important species associated with American tegumentary leishmaniasis and the main agent in Brazil, with variable sensitivity to available drugs. The search for new therapeutic alternatives to treat leishmaniasis is an urgent need, especially for endemic countries. Not only is q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…They suggested that QUE’s antileishmanial effects on amastigotes involve activating Nrf2/HO-1, followed by modulating labile iron stores, resulting in depleted iron for the replication and survival of L. braziliensis . Recently, Santos et al assessed the oral administration of QUE for the first time in hamsters infected with L. braziliensis , unveiling antiamastigote activity (EC 50 of 21 ± 2.5 µM) (Dos Santos et al 2022 ). A substantial decrease in macrophage viability was observed only at concentrations exceeding 640 µM, with an estimated EC 50 of 478 ± 89 µM and a SI of 22, mirroring our study’s results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that QUE’s antileishmanial effects on amastigotes involve activating Nrf2/HO-1, followed by modulating labile iron stores, resulting in depleted iron for the replication and survival of L. braziliensis . Recently, Santos et al assessed the oral administration of QUE for the first time in hamsters infected with L. braziliensis , unveiling antiamastigote activity (EC 50 of 21 ± 2.5 µM) (Dos Santos et al 2022 ). A substantial decrease in macrophage viability was observed only at concentrations exceeding 640 µM, with an estimated EC 50 of 478 ± 89 µM and a SI of 22, mirroring our study’s results.…”
Section: Discussionmentioning
confidence: 99%
“…These in vivo findings reaffirm the therapeutic potential of QUE for CL and corroborate previous studies in different CL and VL models. In Santos et al’s study, it was shown that administering oral QUE (20 mg/kg; five times a week) to hamsters infected with L. braziliensis , starting 7 days after infection for 8 weeks, effectively controlled the lesion size and reduced the parasite load in both the lesion and the draining lymph node (Dos Santos et al 2022 ). In another study, histopathological analysis revealed a reduction in inflammatory cell count, an increase in fibroblasts, and enhanced collagen deposition in tissue sections from mice infected with L. major and subjected to oral QUE treatment at a dosage of 50 mg/kg for 28 consecutive days (Almadani et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that Que had a dose-dependent cytotoxicity against both L. braziliensis promastigotes and amastigotes [ 28 ]. However, several studies have shown that Que had lower antileishmanial activity than amphotericin B [ 24 , 27 ], SSG [ 25 ], and miltefosine [ 28 ]. Compared to mammalian cell lines, Leishmania promastigotes are more susceptible to the inhibitory effects of Que ( Table 2 ).…”
Section: Leishmania Sppmentioning
confidence: 99%
“…In a recent study, treatment of L. braziliensis -infected hamsters with oral Que (20 mg/kg, five times a week), for eight weeks starting from the first week of infection, significantly decreased lesion thickness and parasite load [ 28 ]. However, oral Que exhibited lower in vivo efficacy compared to intraperitoneal Glucantime® (80 mg/kg, three times a week).…”
Section: Leishmania Sppmentioning
confidence: 99%
See 1 more Smart Citation